Bacteria and Viruses: The Bogeymen in the Intensive Care Unit - Kayingo, Gerald (Physician Assist Clin, 2019)
This article covers the frequently encountered bacteria and viruses in the ICU. It focuses on recognition, management, and prevention. Emerging and difficult-to-treat organisms are covered in detail.